Satellite pictures in the study of snow hydrology over Western Himalayas - SRINIVASAN, V.; RAMAN, S. (MAUSAM, 1972)
Satellite APT pictures for the past few years were examined to study snow cover and snowline over the Western Himalayas. Selected pictures for different months were studied ill detail and a suitable method of snow measurements over the Himalayas for operational use was evolved. The results obtained relate to snow cover, appearance of snow snowline and its variations from place to place. The periods of maximum and minimum snow cover and maximum Snow melt are pointed out. The activity of western disturbances with reference to snow cover in winter and the water budget of the Himalayan rivers in Summer are also touched upon. The snowline measurements compare well with the measurements made by other methods-Gemini V pictures, trigonometrical observations and estimates by ground-based personnel. At times in winter, the snowline comes down as low as 900 m a.s.I. An interesting observation is the location of snowline at a higher elevation on the Tibetan side than on the Indian side. The influence of thick glaciers on the snowline in the west Uttar Pradesh region of the Himalayas is pointed out. The accuracy of the various measurements involved in the method are also discussed in detail. The study establishes the feasibility of reliable measurements of the Himalayan snow from APT pictures and focusses attention on the vast wealth of data that can be derived from these pictures.